Assessing the E-Banking Services Using Service Quality and Customer Planned Behavior - Aluma, Ikechukwu Amos; Drequito, Glory Sotelo; Umeh, Azubuike Lucky (Asian Journal of Management Analytics, 2025)
This paper investigates the customer satisfaction of e-banking users by employing the SERVQUAL model and the Theory of Planned Behavior (TPB) model, comprehensively analyzing customer perceptions and behaviors. A quantitative method utilizing a descriptive survey research design was employed to collect and analyze the respondents' e-banking level of satisfaction across SERVQUAL dimensions and TPB constructs. The study revealed that e-banking users expressed high customer satisfaction with e-banking services, as measured using the SERVQUAL dimension and TPB constructs. However, network issues and cyber threats emerge as critical problems that e-banking users encounter. The study provides valuable insights for banks to continuously improve their security features, interface design, and real-time assistance to reduce the anxiety users experience while transacting on e-banking platforms.